2011
DOI: 10.1111/j.1462-5822.2011.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

In search of Brucella abortus type IV secretion substrates: screening and identification of four proteins translocated into host cells through VirB system

Abstract: SUMMARY Type IV secretion systems (T4SS) are specialized protein complexes used by many bacterial pathogens for the delivery of effector molecules that subvert varied host cellular processes. Brucella spp. are facultative intracellular pathogens capable of survival and replication inside mammalian cells. Brucella T4SS (VirB) is essential to subvert lysosome fusion and to create an organelle permissive for replication. One possible role for VirB is to translocate effector proteins that modulate host cellular fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 71 publications
(110 reference statements)
4
116
0
1
Order By: Relevance
“…This is the mechanism by which they mediate secretion. An intriguing observation in several bacteria with T4SSs is that they are able to secrete and/or translocate substrates that are present in the cytoplasm, the periplasmic space, or even inserted in the inner membrane (6,7,11,(15)(16)(17)26). These reports raise issues regarding the initial models that proposed that the T4SSs engage their substrates in the cytoplasm and should encourage the search for alternative models.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This is the mechanism by which they mediate secretion. An intriguing observation in several bacteria with T4SSs is that they are able to secrete and/or translocate substrates that are present in the cytoplasm, the periplasmic space, or even inserted in the inner membrane (6,7,11,(15)(16)(17)26). These reports raise issues regarding the initial models that proposed that the T4SSs engage their substrates in the cytoplasm and should encourage the search for alternative models.…”
Section: Discussionmentioning
confidence: 90%
“…We showed that this new effector protein is secreted in a VirB-dependent manner, that its inactivation affects the intracellular trafficking particularly during the initial stages, and that its secretion involves a periplasmic intermediate (6). Although in Brucella this was the first report identifying a VirB substrate with a twostep secretion process involving a periplasmic intermediate, it was reported that other effectors have a predicted periplasmic signal peptide or putative transmembrane domains (5,7,8). We report here the identification in Brucella of a homologue of the A. tumefaciens virJ gene and characterized this gene genetically and biochemically.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Examples are (1) VceA and VceC, which belong to the VjbR regulon, consequently having their expression coregulated with the VirB T4SS (de Jong et al 2008); (2) BPE123, whose translocation additionally depends on a Sec-secretion signal at the amino terminus; and (3) BPE005, BPE275, and BPE043 (Table 1) (Marchesini et al 2011). Other putative effectors with indefinite positively charged amino acid carboxy-terminal sequences are (1) RicA, which is the sole effector having an assigned host partner, the guanosine di-phosphate (GDP)-bound form of the small GTPase Rab2 (de Barsy et al 2011); (2) Btp1 (TcpB in B. melitensis), which regulates innate immune responses via its Toll/interleukin-1 receptor (TIR) domain (Cirl et al 2008;Salcedo et al 2008) and possibly modulates microtubule dynamics (Radhakrishnan et al 2011); (3) PrpA, a proline-racemase family member, which regulates immune responses (Spera et al 2006); (4) CstA (conserved Sec24A-targeted protein A), which controls Brucella intracellular trafficking (de Barsy et al 2012); and (5) BvfA, which is required for Brucella intracellular replication (Lavigne et al 2005).…”
Section: Machineries Indispensable For Host Interactionsmentioning
confidence: 99%